Bio-Ecological Diversity vs. Socio-Economic Diversity: A Comparison of Existing Measures - Carole Maignan; Gianmarco Ottaviano; Dino Pinelli; Francesco Rullani (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper aims to enrich the standard toolbox for measuring diversity in economics. In so doing, we compare the indicators of diversity used by economists with those used by biologists and ecologists. Ecologists and biologists are concerned about biodiversity: the diversity of organisms that inhabit a given area. Concepts of species diversity such as alpha (diversity within community), beta (diversity across communities) and gamma (diversity due to differences among samples when they are combined into a single sample) have been developed (Whittaker, 1960). Biodiversity is more complex than just the species that are present, it includes species richness and species evenness. Those various aspects of diversity are measured by biodiversity indices such as Simpson's Diversity Indices, Species Richness Index, Shannon Weaver Diversity Indices, Patil and Taillie Index, Modified Hill's Ratio. In economics, diversity measures are multi-faceted ranging from inequality (Lorenz curve, Gini coefficient, quintile distribution), to polarisation (Esteban and Ray, 1994; Wolfon, 1994, D'Ambrosio (2001)) and heterogeneity (Alesina, Baqir and Hoxby, 2000). We propose an interdisciplinary comparison between indicators. We review their theoretical background and applications. We provide an assessment of their possible use according to their specific properties.
Keywords: C1; Z10; 330; Diversity; Growth; Knowledge; Artenvielfalt; Konzentrationsmaß; Vergleich; Biowissenschaften; Ökologie; Wirtschaftswissenschaft; Theorie; Maßzahl